2014
DOI: 10.1021/jp508150w
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Approaches To Elucidate the Structures of Silver Clusters inside the ZSM-5 Cavity

Abstract: A combination of experimental and computational analyses suggested the presence of Ag3 or Ag4 clusters inside a nanometer-sized cavity in Ag–ZSM-5 zeolites, which were formed from H–ZSM-5 using the conventional ion-exchange method in an aqueous silver nitrate solution. During the experimental analyses, we investigated the structural and absorption properties of Ag–ZSM-5 through UV–vis diffuse reflectance and X-ray absorption fine structure (XAFS) measurements. The results from the extended XAFS (EXAFS) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 116 publications
4
43
0
Order By: Relevance
“…47 Previously, we combined UV-vis measurements with density functional theory (DFT) calculations to elucidate the state of silver atoms within ZSM-5 zeolites, whose ten-membered rings cavities are on the nanometre scale. 48,49 UV-vis measurements in previous studies found maximum peaks ranging from 300-320 nm. 43,49 These peaks can be assigned by electronic transitions of triangle Ag 3 and buttery Ag 4 clusters inside ZSM-5, whose structures were optimized by DFT calculations (Fig.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…47 Previously, we combined UV-vis measurements with density functional theory (DFT) calculations to elucidate the state of silver atoms within ZSM-5 zeolites, whose ten-membered rings cavities are on the nanometre scale. 48,49 UV-vis measurements in previous studies found maximum peaks ranging from 300-320 nm. 43,49 These peaks can be assigned by electronic transitions of triangle Ag 3 and buttery Ag 4 clusters inside ZSM-5, whose structures were optimized by DFT calculations (Fig.…”
Section: Introductionmentioning
confidence: 88%
“…48,49 UV-vis measurements in previous studies found maximum peaks ranging from 300-320 nm. 43,49 These peaks can be assigned by electronic transitions of triangle Ag 3 and buttery Ag 4 clusters inside ZSM-5, whose structures were optimized by DFT calculations (Fig. S1 (ESI †)).…”
Section: Introductionmentioning
confidence: 88%
“…Previously, our studies confirmed that this B3LYP-optimized MFI zeolite model comprised of 10-MR in cavities reproduced well the experimentally observed data. [12][13][14]22,[24][25][26][27][28][29][30][31] Taking our previous studies into consideration, we used the M7 site for the Al substitution position; 32 and we defined the Al configuration as the [M7-S2] arrangement. [12][13][14]30 To optimize fully the larger MFI geometry with a 10-MR cavity, we used the 6-311G(d) basis set for the zinc atom and the 6-31G (d) basis set for the Al atom, as well as four O atoms that were connected to the substituted Al atom.…”
Section: Computational Methodology (Calculation Method)mentioning
confidence: 99%
“…dispersed Ag + cations256 is reestablished and well visualized for AgCHA-R1O and AgCHA-R2O samples. On the other hand, for all RHO-based samples the typical band of Ag + species is shown while a quite similar band centered at 355 nm attributed as Ag 0 nanoparticles 261 can be seen.…”
mentioning
confidence: 79%
“…The AgCHA RED400 catalyst maintains roughly the same UV-Vis spectrum as in the reduced state after reduction, while the spectrum of AgRHO RED400 was completely changed after reaction. The band present in reduced sample disappeared giving rise to the formation of typical band at 220 nm characteristic of Ag + in exchange positions within the zeolite 256.…”
mentioning
confidence: 99%